2021
DOI: 10.3390/catal11050612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RhCrOx Cocatalyst Loaded on Different Metal Doped LaFeO3 Perovskites with Photocatalytic Hydrogen Performance under Visible Light Irradiation

Abstract: Photocatalytic hydrogen (H2) production by water splitting provides an alternative to fossil fuels using clean and renewable energy, which gives important requirements about the efficiency of photocatalysts, co-catalysts, and sacrificial agents. To achieve higher H2 production efficiencies from water splitting, the study uses different metals such as yttrium (Y), praseodymium (Pr), magnesium (Mg), Indium (In), calcium (Ca), europium (Eu), and terbium (Tb) doped lanthanum iron oxide (LaFeO3) perovskites. They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Other than this, 10% triethanolamine generated 1.38 times improved H 2 as compared to 5% triethanolamine based on the high ability of TEOA for capturing holes, thus leading to the separation of charge carriers for boosted evolution of H 2 . A current study also reported an increasing trend in H 2 generation over TEOA until 20% concentration …”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Other than this, 10% triethanolamine generated 1.38 times improved H 2 as compared to 5% triethanolamine based on the high ability of TEOA for capturing holes, thus leading to the separation of charge carriers for boosted evolution of H 2 . A current study also reported an increasing trend in H 2 generation over TEOA until 20% concentration …”
Section: Resultssupporting
confidence: 72%
“…A current study also reported an increasing trend in H 2 generation over TEOA until 20% concentration. 81 3.2.6. Photostability.…”
Section: Effect Of Sacrificial Agentsmentioning
confidence: 99%
“…Then, Nishioka et al tested Rhodium doping on supported BaTiO3 synthesized by hydrothermal method [107]. In another study, RhCrOx loaded with LaFeO3 cocatalyst was utilizd to closely estimate the performance of photocatalytic hydrogen evolution under solar spectrum [108]. It has been discovered that the rate of H2 production in the vicinity of RhCrOx/Pr-LaFeO3 and triethanolamine (TEOA) as sacrificial agents is the highest compared to methanol and ethanol.…”
Section: Single Noble Metalmentioning
confidence: 99%
“…Semiconductors play a vital role in the efficient solar water splitting. , Currently, the semiconductors applied in photocatalytic water splitting for hydrogen production mainly include transition metal oxides, perovskite-structured materials, sulfides, and polymeric carbon nitride . Among them, ABX 3 perovskite materials are highly regarded by researchers for their structural stability and easy replacement of (AB) metal elements.…”
Section: Introductionmentioning
confidence: 99%